129k views
19 votes
Solve the system of equations by using substitution.​

Solve the system of equations by using substitution.​-example-1
User Chen Ni
by
6.3k points

1 Answer

11 votes

Answer:

(x,y) = (-1,1)

Explanation:

Given the equations

y = 2x + 3

x - y = -2

substitute the value of y in the first equation into the second

x - (2x + 3) = -2

x -2x - 3 = -2

-x - 3 = -2

add 3 to both sides

-x = -2 + 3

- x = 1

Divide both sides by -1

x = -1

Substitute into the first equation

y = 2(-1) + 3

y = -2 + 3

y = 1

User Danield
by
7.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.